Emerging roles of Atypical Chemokine Receptor 3 (ACKR3) in normal development and physiology - Quinn, K.E. (Cytokine, 2018)
The discovery that atypical chemokine receptors (ACKRs) can initiate alternative signaling pathways rather than classical G-protein coupled receptor (GPCR) signaling has changed the paradigm of chemokine receptors and their roles in modulating chemotactic responses. The ACKR family has grown over the years, with discovery of new functions and roles in a variety of pathophysiological conditions. However, the extent to which these receptors regulate normal physiology is still continuously expanding. In particular, atypical chemokine receptor 3 (ACKR3) has proven to be an important receptor in mediating normal biological functions, including cardiac development and migration of cortical neurons. In this review, we illustrate the versatile and intriguing role of ACKR3 in physiology.